Indonesian Bus Stations: Mixed-Use, Government Capital Funding, and Its Determinants and Impact - Achyani, Fatchan; Riyardi, Agung (Universitas Muhammadiyah Surakarta, 2023)
The main issues of this research are the determinants and impact of the government capital funding on mixed-use bus station. These issues raise research objectives about the definition of mixed-use bus station, the determinants of government capital funding on bus station, and its impact to bus station production. To achieve the objectives, two methods are employed. The first is the description method that applies Cartesian Diagram to define mixed-use bus station. The second is the association methods that applies the government capital funding determinants and impact econometric models. The variables for the first method are passengers and buses arrived at and departed from monitored bus station during 2023 Eid Al-Fitr holidays, while the variables for the second method are government capital funding on bus station, bus station production, bus station usage partnership, type of bus station, and local economy. The results show that twenty-four bus stations are mixed-use bus station, the determinants of government capital funding are mixed-use type and bus station usage partnership, and the impact of government capital funding is bus station production that is suffered by local economy.